The actors involved and the decision-making process used in the exploitation of university patents - Ismail, Kamariah; Mason, Colin; Cooper, Sarah; Wan Omar, Wan Zaidi; Abdul Majid, Izaidin (2008)
The commercialisation of university patents via licensing to established companies or to spin-off formations is the method commonly used by universities to exploit their patents. This paper looks very closely at this process, based on the authors’ case study at a university in Scotland where 12 patents or inventors were selected for scrutiny. The study focuses on the actors involved and the decision-making processed used by this university regarding exploitation of its portfolio of patents. The findings show that the actors involved were the inventors themselves, industry, and the university’s Technology Transfer Office (TTO), or any two of these parties. The decision to commercialise patents via spin-off formations was influenced by factors such as how well the inventors recognised the commercial potential of their technologies and how motivated they were to see their inventions exploited through entrepreneurial efforts. The decision to commercialise patents via licensing to established companies, however, was made individually by one or more of the three actors involved. The significant difference in the latter instance was that the inventors were not motivated to be entrepreneurs, and were unwilling to take risks in a new business venture. The findings also show that the TTO did not have a special due diligence system to help inventors identify commercial opportunities. The lack of skills, capabilities, and marketing efforts on the part of the TTO in all sectors resulted in the decision to form spin-offs that were based on the inventors’ motivation and industry experience.